1990
DOI: 10.1177/074193259001100408
|View full text |Cite
|
Sign up to set email alerts
|

Parental Satisfaction with Integrated Class Placements of Special Education and General Education Students

Abstract: Parents' satisfaction with their children's academic and social progress is an important consideration for schools planning to increase the number of classrooms offering fully integrated programs for special education students. The survey reported here compared satisfaction ratings from parents of special education students and parents of general education students whose children were placed in integrated elementary classrooms. Both groups of parents rated their initial response and their satisfaction 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…Due to the unavailability of research dealing specifically with perceptions of parents whose children display significant cognitive delays, these components and individual PATI Scale question items were based on studies associated with the related topics of parent perceptions of (a) the placement of their children with severe (Hunt et aI., 1993;McDonnell, 1987) or mild to moderate (Guralnick et aI., 1995;Miller et aI., 1992) disabilities into special education programs on general education campuses as opposed to segregated sites; (b) the integration of children with sensory impairments (Giangreco et aI., 1991) or mild to moderate disabilities (Hayes & Gunn, 1988;Lowenbraun & Affleck, 1990;Mlynek et al, 1982) into general education classrooms; and (c) normalization and community placement practices (Ferrara, 1979;Larson & Lakin, 1991;Tausig, 1989;Thurman & Fiorelli, 1979).…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unavailability of research dealing specifically with perceptions of parents whose children display significant cognitive delays, these components and individual PATI Scale question items were based on studies associated with the related topics of parent perceptions of (a) the placement of their children with severe (Hunt et aI., 1993;McDonnell, 1987) or mild to moderate (Guralnick et aI., 1995;Miller et aI., 1992) disabilities into special education programs on general education campuses as opposed to segregated sites; (b) the integration of children with sensory impairments (Giangreco et aI., 1991) or mild to moderate disabilities (Hayes & Gunn, 1988;Lowenbraun & Affleck, 1990;Mlynek et al, 1982) into general education classrooms; and (c) normalization and community placement practices (Ferrara, 1979;Larson & Lakin, 1991;Tausig, 1989;Thurman & Fiorelli, 1979).…”
Section: Instrumentmentioning
confidence: 99%
“…In accordance with the historical pattern of leadership within the inclusion movement, the bulk of the literature regarding parent perceptions and attitudes has focused on inclusive practices for children with mild or moderate disabilities (i.e. Hayes & Gunn, 1988;Lowenbraun & Affleck, 1990;Mlynek, Hannah, & Hamlin, 1982). Further, scales designed to measure attitudes toward inclusive practices have been concerned with perceptions of educators rather than parents, and address the perceived efficacy of inclusion of students identified with mild (Semmel et aI., 1991) or unspecified (Anotonak & Larrivee, 1995;Larrivee, 1992;Schmelkin, 1981;Wilczenski, 1992) disabilities rather than those with severe disabilities.…”
mentioning
confidence: 96%
“…In a later survey (Simpson & Miles, 1989), only 25% of the parents of children with learning and behavioural difficulties were willing to support 'mainstreaming' without guarantees of additional resources. In an American study, Lowenbraun, Madge and Affleck (1990) surveyed parents of 'mildly mentally handicapped' children and, although it was found that 88% were satisfied with the placement of their child in mainstream classrooms, parents of children who had previously been in resource room placements were slightly more satisfied than they were with their current mainstream placement. A review of these and other surveys led Hornby, Atkinson and Howard (1997) to conclude that parents are neither 'overwhelmingly for' nor 'against' the practice of 'integration/inclusion'.…”
Section: Mainstream Inclusion: Some Limitations Of the Conceptmentioning
confidence: 87%
“…Further, the bulk of the literature regarding parent perceptions and attitudes has focused on inclusive practices for children with mild or moderate disabilities (i.e., Hayes & Gunn, 1988;Lowenbraun & Affleck, 1990;Mlynek, Hannah, & Hamlin, 1982) rather than students with significant disabilities. However, since inclusive programming for students with significant disabilities is likely to be controversial (Borthwick-Duffy et al, 1996) and often requires a great degree of program planning, an understanding of parent preferences regarding this population is particularly needed.…”
mentioning
confidence: 99%